Political Contexts and Their Visualizations in the Animated Films of Communist Yugoslavia - Wilczyńska, Patrycja; Leonowicz-Bukała, Iwona (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
In the second half of the 20th century, Zagreb, Croatia, was one of the most important centres of film animation in Europe, and a key role in its development was played by the Zagreb Film Studio, which has been operating continuously since 1953. The creators associated with Zagreb Film Studio are often called the Zagreb School of Animation, a term referring to their unique style. The Studio became famous primarily for its short animations, which were distinctive due to an innovative approach in terms of both technique and narrative. Zagreb Film productions have won numerous festival awards and international recognition. An important context for the development of the Studio was the political situation in communist Yugoslavia, which influenced the themes and aesthetics of the films. This article analyses the political context of the Studio’s activity and how it was visualized in Yugoslavian animation.